DEVELOPMENT AND CHARACTERIZATION OF ENDOPHYTE-FREE TALL FESCUE VARIETY, GREENMASTER3ho - Sang-Hoon Lee; Ki-Yong Kim; Hee Jung Ji; Tae Young Hwang; Hyung Soo Park; Hyun Seok Chae; Ki-Won Lee (Journal of Animal and Plant Sciences, 2016)
A new tall fescue variety (Festuca arundinacea Schreb.), named Greenmaster 3ho, was developed by the National Institute of Animal Science, Rural Development Administration in Republic of Korea from 2010 to 2014. For synthetic seed production of this new variety, five superior clones, 09XFa02, 09XFa03, 09XFa11, 09XFa13, and 09XFa14 were selected and polycrossed. The agronomic growth characteristics and forage production capability of the seeds were studied at Cheonan from 2010, and regional trials were conducted in Cheonan, Hoengseong, Jeju, and Jinju from 2012 to 2014. Greenmaster3ho showed enhanced disease resistance, persistence, and regrowth ability as compared to Fawn. The dry matter yield of Greenmaster3ho was 29% higher (15,119 kg/ha) than that of Fawn. However, the nutritive value of both varieties was similar. This study developed a new tall fescue variety with excellent environmental adaptability, aiming to make a contribution to the vitalization of the Korean grassland industry.
Keywords: Tall fescue; Variety; Greenmaster 3ho; Grassland; Breeding